2023
DOI: 10.3390/dj11070168
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Apical Periodontitis Disease in the Development of Bisphosphonate-Related Osteonecrosis of the Jaw: An Animal Study

Abstract: Background: Microorganisms and their by-products are responsible for establishing pulpal and periapical diseases. Healing is compromised in patients under bisphosphonate therapy, and the presence of periapical infections can potentially lead to the development of medication-related osteonecrosis of the jaw (MRONJ). This work aimed to evaluate if bisphosphonate therapy is a risk factor for MRONJ development in the presence of periapical lesions. Methods: Two groups of 10 female Wistar rats were used. The experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…54 Marques-Ferreira et al found that in patients without osteoporosis and the presence of zoledronate therapy, periapical lesions had lower bone resorption compared to the control group. 55…”
Section: Bisphosphonates-zoledronatementioning
confidence: 99%
“…54 Marques-Ferreira et al found that in patients without osteoporosis and the presence of zoledronate therapy, periapical lesions had lower bone resorption compared to the control group. 55…”
Section: Bisphosphonates-zoledronatementioning
confidence: 99%